2009
DOI: 10.1183/09031936.00003709
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in bronchiectasis: a long-term study assessing the factors influencing survival

Abstract: There is little literature about the mortality associated with bronchiectasis. The aim of the present study was to investigate factors affecting mortality in patients with bronchiectasis.In total, 91 patients were examined for aetiology, pulmonary function tests, high-resolution computed tomography, sputum microbiology and quality of life scores and were then followed over 13 yrs.Overall, 29.7% of the patients died. On multivariate analysis, age, St George's Respiratory Questionnaire activity score, Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
271
5
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(313 citation statements)
references
References 28 publications
27
271
5
10
Order By: Relevance
“…A recent study followed 91 patients with bronchiectasis enrolled in a clinical study for 13 years and found a mortality rate of 29.7% (26). Independent predictors of mortality in this cohort included age, P. aeruginosa colonization, pulmonary function, and the St. George's respiratory questionnaire, all of which support the findings of the present study (26).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A recent study followed 91 patients with bronchiectasis enrolled in a clinical study for 13 years and found a mortality rate of 29.7% (26). Independent predictors of mortality in this cohort included age, P. aeruginosa colonization, pulmonary function, and the St. George's respiratory questionnaire, all of which support the findings of the present study (26).…”
Section: Discussionsupporting
confidence: 79%
“…Independent predictors of mortality in this cohort included age, P. aeruginosa colonization, pulmonary function, and the St. George's respiratory questionnaire, all of which support the findings of the present study (26). Onen and colleagues reported data from 98 patients with bronchiectasis in which there were 16 deaths and found age, BMI, and severity of dyspnea to be the strongest predictors of mortality (27).…”
Section: Discussionsupporting
confidence: 76%
“…Various studies on patients with non-CF bronchiectasis have demonstrated the relationship of both these variables with an increase in mortality [12,13]. The high colinearity between FEV1 and forced vital capacity made it possible to choose FEV1 to represent the patient's functional state, as this is the variable most commonly used in the evaluation of airflow obstruction, the most common functional pattern in patients with bronchiectasis [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Several single variables have been used to predict key outcomes of bronchiectasis, such as decline in lung function, various clinical parameters, radiological extension and the presence of chronic colonisation by Pseudomonas aeruginosa [9,12,13]. However, as with other airways diseases, the severity and prognosis of bronchiectasis cannot be adequately defined with one single variable.…”
Section: Introductionmentioning
confidence: 99%
“…The lower rate of colonization by this germ in this group can be one of the reasons for this finding. (16) Another fact that has been well established in the literature is that, in patients with bronchiectasis, the colonization by Staphylococcus aureus is related to a higher probability of CF diagnosis. (17) The mean age at diagnosis in CF individuals was 14 years, which was considered late diagnosis.…”
mentioning
confidence: 99%